Copper-61 is an advantageous alternative to gallium-68 for PET imaging of somatostatin receptor-expressing tumors: a head-to-head comparative preclinical study - Basaco Bernabeu, Tais; Mansi, Rosalba; Del Pozzo, Luigi; Gaonkar, Raghuvir Haridas; McDougall, Lisa; Johayem, Anass; Blagoev, Milen; De Rose, Francesco; Jaafar-Thiel, Leila; Fani, Melpomeni (Frontiers in Nuclear Medicine, 2024)
Background: 68Ga-PET with the two registered somatostatin analogs [68Ga]Ga-DOTA-TOC and [68Ga]Ga-DOTA-TATE is routinely used for imaging of somatostatin receptor (SST)-expressing neuroendocrine tumors. We investigated copper-61 as an alternative radiometal for PET imaging of SST-expressing tumors. Compared to gallium-68, copper-61 (t1/2 = 3.33h, Eβ+max = 1.22 MeV) can be produced in large scale, enables late time point imaging, and has the therapeutic twin copper-67. Herein, DOTA-TOC and NODAGA-TOC were labeled with copper-61 and compared with the clinically used [68Ga]Ga-DOTA-TOC. Methods: [61Cu]CuCl2 was produced from an irradiated natural Ni-target. DOTA-TOC and NODAGA-TOC were labeled with [61Cu]CuCl2 in ammonium acetate buffer at pH 5-6 and 95°C (DOTA-TOC) or room temperature (NODAGA-TOC). The radioligands were evaluated head-to-head in vitro using HEK-SST2 cells (affinity, binding sites, cellular uptake and efflux) and in vivo using HEK-SST2 xenografts (PET/CT imaging, biodistribution and pharmacokinetics), and compared to [68Ga]Ga-DOTA-TOC. Dosimetry estimates were made for [61Cu]Cu-NODAGA-TOC. Results: [61Cu]Cu-DOTA-TOC and [61Cu]Cu-NODAGA-TOC were prepared at an apparent molar activity of 25 MBq/nmol, with radiochemical purity ≥96% and ≥98%, respectively. In vitro, both presented sub-nanomolar affinity for SST2 (IC50 = 0.23 and 0.34 nM, respectively), they were almost entirely internalized upon binding to SST2-expressing cells, and had alike efflux rate at 37°C. In vivo, [61Cu]Cu-DOTA-TOC and [61Cu]Cu-NODAGA-TOC showed the same accumulation in SST2-expressing tumors. However, PET/CT images and biodistribution studies clearly showed an unfavorable biodistribution for [61Cu]Cu-DOTA-TOC, characterized by accumulation in the liver and the abdomen.[61Cu]Cu-NODAGA-TOC displayed favorable biodistribution, comparable with [68Ga]Ga-DOTA-TOC at 1h p.i. Notwithstanding, [61Cu]Cu-NODAGA-TOC showed advantages at 4h p.i., due to the tumor retention and the improved tumor-to-nontumor ratios. The effective dose (2.41E-03 mSv/MBq) of [61Cu]Cu-NODAGA-TOC, but also the dose to the other organs and the kidneys (9.65E-02 mGy/MBq), suggested a favorable safety profile. Somatostatin receptor 61Cu-PET imaging not only matches the performance of 68Ga-PET at 1h p.i. but becomes advantageous at late-time imaging of 4h p.i., as it provides improved better tumor-to-non tumor ratios. [61Cu]Cu-NODAGA-TOC is superior to [61Cu]Cu-DOTA-TOC in vivo. The use of the chelator NODAGA allows quantitative labeling with copper-61 at room temperature and enables the straightforward use of kit formulation for simple manufacturing in medical centres.